2019
DOI: 10.1590/s2179-975x8118
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the embryotoxicity in zebrafish (Danio rerio) of the flocculant and coagulant compounds used for water remediation

Abstract: Aim: Leaching from mining activities reaches water bodies, causing water contamination and acidification by toxic metals. As a consequence, oxygen depletion occurs, with the disappearance of certain benthic organisms, losses in phytoplankton and zooplankton biomass, and fish mortality. Remediation of contaminated water from mining involves the use of flocculants based on acrylamide monomers and polyacrylamide and of coagulants based on aluminum. Our aim was to assess the aquatic toxicity of the flocculant WF 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Several recent studies have shown that ACR causes acute neurotoxicity in the developmental stage of zebrafish when exposed to nearly 1 mM ACR for 3 days (Faria et al 2018(Faria et al , 2019aPark et al 2021). Moreover, ACR could be genotoxic to Carassius auratus at levels 50-150 mg/L, shows hemato-toxicity (such as induced anemia, red blood cell count reduction, low hemoglobin level, and decreased packed cell volume) in Clarias gariepinus at concentrations from 26.6 up to 106.4 mg/L (Ibrahim and Ibrahem 2020), and induces cardiac developmental toxicity at levels from 71 to 203 mg/L, cardiovascular toxicity at concentrations from 35.5 to 203 mg/L, retinal toxicity (71-142 mg/L), splenic toxicity (12.8 mg/kg), and oxidative stress (142 mg/L) in Danio rerio (Moura et al 2019;Singh et al 2019;Spencer et al 2018). Besides, many studies have shown a lethal concentration of ACR in several fish species (Gopika et al 2018b;Krautter et al 1986;Larguinho et al 2014b;Moura et al 2019;Shanker and Seth 1986;Spencer et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have shown that ACR causes acute neurotoxicity in the developmental stage of zebrafish when exposed to nearly 1 mM ACR for 3 days (Faria et al 2018(Faria et al , 2019aPark et al 2021). Moreover, ACR could be genotoxic to Carassius auratus at levels 50-150 mg/L, shows hemato-toxicity (such as induced anemia, red blood cell count reduction, low hemoglobin level, and decreased packed cell volume) in Clarias gariepinus at concentrations from 26.6 up to 106.4 mg/L (Ibrahim and Ibrahem 2020), and induces cardiac developmental toxicity at levels from 71 to 203 mg/L, cardiovascular toxicity at concentrations from 35.5 to 203 mg/L, retinal toxicity (71-142 mg/L), splenic toxicity (12.8 mg/kg), and oxidative stress (142 mg/L) in Danio rerio (Moura et al 2019;Singh et al 2019;Spencer et al 2018). Besides, many studies have shown a lethal concentration of ACR in several fish species (Gopika et al 2018b;Krautter et al 1986;Larguinho et al 2014b;Moura et al 2019;Shanker and Seth 1986;Spencer et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ACR could be genotoxic to Carassius auratus at levels 50-150 mg/L, shows hemato-toxicity (such as induced anemia, red blood cell count reduction, low hemoglobin level, and decreased packed cell volume) in Clarias gariepinus at concentrations from 26.6 up to 106.4 mg/L (Ibrahim and Ibrahem 2020), and induces cardiac developmental toxicity at levels from 71 to 203 mg/L, cardiovascular toxicity at concentrations from 35.5 to 203 mg/L, retinal toxicity (71-142 mg/L), splenic toxicity (12.8 mg/kg), and oxidative stress (142 mg/L) in Danio rerio (Moura et al 2019;Singh et al 2019;Spencer et al 2018). Besides, many studies have shown a lethal concentration of ACR in several fish species (Gopika et al 2018b;Krautter et al 1986;Larguinho et al 2014b;Moura et al 2019;Shanker and Seth 1986;Spencer et al 2018). Recently, Ligina et al (2022) exhibited that ACR at sublethal levels (13.4 µg/L) induced alteration in hematological indices and suppressed redox status in gill tissue of the A. testudineus fish.…”
Section: Introductionmentioning
confidence: 99%
“…This makes zebra fish embryos a helpful tool to investigate other toxicology analysis diversions that produce an immediate result. The frequent use of zebra fish embryo is usually due to its short life span-speedy and influential outcomes [4,5]. Zebra fish embryos have a rapid process of embryogenesis and contain several eggs.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few are in excellent or acceptable compliance to wastewater treatment standards. To monitor the effect of water remediation efforts, previous studies have tested water remediation agents such as flocculants and coagulants using zebrafish models (Faria et al,2018a;Moura et al,2019). However, the safety of water remediation methods used in developing countries is still not well understood.…”
Section: Introductionmentioning
confidence: 99%